2009
DOI: 10.1111/j.1939-1676.2008.0240.x
|View full text |Cite
|
Sign up to set email alerts
|

Adenohypophyseal Function in Dogs with Primary Hypothyroidism and Nonthyroidal Illness

Abstract: Background: A recent study of dogs with induced primary hypothyroidism (PH) demonstrated that thyroid hormone deficiency leads to loss of thyrotropin (TSH) hypersecretion, hypersomatotropism, hypoprolactinemia, and pituitary enlargement with large vacuolated ''thyroid deficiency'' cells that double-stained for growth hormone (GH) and TSH, indicative of transdifferentiation of somatotropes to thyrosomatropes.Hypothesis: Similar functional changes in adenohypophyseal function occur in dogs with spontaneous PH as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…The high basal serum GH and IGF-1 concentrations in hypothyroid dogs were consistent with findings of other studies [14][15][16] in this species. Serum GH concentration is reportedly high in hypothyroid humans with insulin resistance, 10 but other studies [64][65][66] in hypothyroid humans have revealed no change or a decrease in serum GH concentrations or response to GHRH.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The high basal serum GH and IGF-1 concentrations in hypothyroid dogs were consistent with findings of other studies [14][15][16] in this species. Serum GH concentration is reportedly high in hypothyroid humans with insulin resistance, 10 but other studies [64][65][66] in hypothyroid humans have revealed no change or a decrease in serum GH concentrations or response to GHRH.…”
Section: Discussionsupporting
confidence: 93%
“…For example, in hypothyroid insulin-resistant women, plasma concentrations of glucagon, epinephrine, cortisol, and GH were high before hormone replacement therapy, indicating that these hormones may contribute to the development of insulin resistance. 10 Growth hormone excess has been linked to insulin resistance in dogs, cats, and people, [11][12][13] and recent studies [14][15][16] have revealed high GH concentrations in hypothyroid dogs. Obesity, which is a common consequence of the reduced metabolism of hypothyroid dogs, may also negatively affect S I and glucose tolerance in dogs.…”
Section: Air Gmentioning
confidence: 98%
“…and hypothyroidism and diabetes mellitus can occur together (Hess et al, 2003;Dixon et al, 1999). Increased concentrations of IGF-1 and GH have been documented in hypothyroid dogs and likely contribute to insulin resistance (Diaz-Espiñeira, 2009;Hofer-Inteeworn, 2012). Increased concentrations of IGF-1 and GH have been documented in hypothyroid dogs and likely contribute to insulin resistance (Diaz-Espiñeira, 2009;Hofer-Inteeworn, 2012).…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…Absence of an increase in plasma TSH concentration after TRH administration is not fully diagnostic for central hypothyroidism. Also in dogs with primary hypothyroidism, TRH administration does not result in a significant rise in plasma TSH concentration . In 5 of the dogs, the central nature of the hypothyroidism was confirmed by administering rhTSH on 3 consecutive days .…”
Section: Discussionmentioning
confidence: 89%
“…Differentiating primary and central hypothyroidism is problematic because TSH deficiency in central hypothyroidism results in atrophy of the thyroid gland, with resultant inadequate thyroxine secretion or radionuclide uptake on TSH stimulation testing and nuclear scintigraphy, respectively . The relatively low sensitivity of increased plasma TSH concentration in dogs with primary hypothyroidism contributes to the difficulty in the diagnosis of central hypothyroidism.…”
Section: Discussionmentioning
confidence: 99%